Challenges in Asian Cotton FibreÂ Quality and Future Requirement - PATIL, P. G.; MANDHYAN, P. K.; SUNDARAMOORTHY, C.; ARPUTHARAJ, A. (Cotton Research Journal, 2021)
Cotton is very important natural fibre in terms of production, value and employment generation. Asian countries play an important role in production and the trade of cotton, accounting for about two-thirds (66.8%) of worldwide cotton imports. Cotton fibre quality requirement varies for different spinning systems with the developments of modern machines. Due to high automation in spinning machines, contamination free cotton is required for better yarn production. Fibre quality improvement in G.arboreum cotton in terms of length and in G.barbadense in terms of strength is the utmost need for Asian cotton. Cotton fibre faces stiff competition from synthetic (man made) fibres. It is very important to improve the characteristics of cotton, like higher strength, crease resistance, flame retardance, etc. using breeding technologies for the better co-existence of cotton with polyester in the textile apparel industry. This paper discusses the challenges in Asian cotton fibre quality requirements and attempts to give the possible solutions for the same.